Price premiums for organic pasta and pasta produced in Sweden : a hedonic pricing approach - Nilsson, Hanna; Vahtra, Julia (SLU/Dept. of Economics, 2017)
Due to the growing interest for organically and locally produced food, several studies based on consumers’ stated preferences regarding organic and Swedish-produced food products have been conducted. However, attitudes and preferences do not always convert into actions, causing a void in the research (Jörgensen, 2011). This thesis aims to detect whether the Swedish consumers are willing to pay a price premium for organic and Swedish-produced pasta, based on revealed preferences. To determine the price premiums the hedonic pricing method is applied. The dataset includes 305 observations from different geographical areas in Sweden: Uppsala, Malmö, Bunkeflostrand, Stockholm, Limhamn, Norrköping and Göteborg. The price premiums obtained for the attributes “organic pasta” and “Swedish-produced pasta” were 7,9 SEK/kg and 2,3 SEK/kg respectively, nevertheless the price premium for “Swedish-produced pasta” did not show any significance in the model. The Swedish government has an ambition of increasing the organically certified farmland with 30 % to 2030 (Näringsdepartementet, 2017). Hence the results serve as an incentive for the farmers to increase their organic production, which is conformable with the government’s goal. In addition, the results provide an indication regarding how the Swedish consumers value the environmental qualities associated with organic food production.